Numerical simulation of crack propagation behavior of a semi-cylindrical specimen under dynamic loading (Fracture and Structural Integrity, 2019)
To design and evaluate the analytical crack propagation of a specimen under dynamic load, measurement of dynamic fracture parameters is necessary. However, analytical methods have significant complexity, and experimental methods are also time-consuming that require high precision and considerable funding. Therefore, numerical methods can be used to solve these problems. The Extended Finite Element Method (X-FEM) as a powerful and efficient tool can be used for this purpose. In this paper, X-FEM code in ABAQUS software was used in order to simulate crack growth in a semi-circular specimen with pre-existed crack and also intact specimen to determine dynamic stress intensity factor (DSIF) using displacement extrapolation method. To verify the numerical modeling output, the curve of crack surface opening displacement (CSOD) in X-FEM model has been compared with the experimental curve. Moreover, concrete damage plastic (CDP) model was used to validate X-FEM simulation results. The results show that the DSIF for a cracked sample under a maximum dynamic load 3000 N is equal to 0.5 Mpa . Comparison between the CDP and X-FEM results showed that in both approaches, the same area for crack propagation was also determined.
Keywords: Extended Finite Element Method (X-FEM); Concrete Damage plastic (CDP); Displacement extrapolation; Dynamic stress intensity factor (DSIF); Crack surface opening displacement (CSOD)